The Pedagogy of Teacher Education in Ethiopia: Reconstructing Understandings and Practices on Teaching about Teaching and Learning to Teach - Mihiretie, Dawit Mekonnen (Bahir Dar Journal of Education, 2023)
There is an argument that Marshal McLuhan’s ‘the medium is the message’ adage is more likely to be underpinned in the context of teacher education since pedagogy is not only a means of delivering content in teacher education but also the content (what) in teachers’ professional preparation. The quality of teacher education depends heavily on the practice of teacher educators and the learning experiences of student teachers: Pedagogy of teacher education. The pedagogy of teacher education is conceptualized as teaching about teaching and learning to teach. Using primary data from teacher educators and student teachers and secondary data sources (documents and research studies), the paper examined and reflected on Ethiopian teacher education pedagogy. Questionnaire, interview and observation were used to collect primary data. The findings revealed ingrained assumptions that student teachers learn to teach by learning theories and facts of different courses through lectures, discussions, and group work. Teacher educators in the study characterized their typical classroom as a combination of ‘reviewing of the previous lesson, explanation, discussion, and lesson summary’ which inherently reflects features of a typical classroom in Ethiopian schools. When asked which pedagogies help student teachers to learn to teach, teacher educators mentioned group work, discussion, lecturing, oral questioning and classwork, quiz, and practicum (ordered in terms of frequencies). It is argued that teaching about teaching and learning to teach are customarily reduced to the delivery and learning of course contents rather than the ‘how’ of teaching through teacher educators’ modeling and reflection, student teachers’ school experiences, or other pedagogies that develop learning to teach among student teachers. Teacher educators’ practices, however, in some cases demonstrated elements of active learning techniques aimed at improving mastery of content and practicing teaching skills. However, their interview responses on preparing teachers largely lack pedagogies relevant to learning to teach. Efforts to improve the quality of education in general and teacher education, in particular, should prioritize the critical examination and reform of teacher educators’ preparation, professional developments, and pedagogical practices at teacher education colleges and universities.